2019
DOI: 10.17535/crorr.2019.0023
|View full text |Cite
|
Sign up to set email alerts
|

A new full-NT step interior-point method for circular cone optimization

Abstract: We present a full step feasible interior-point algorithm for circular cone optimization using Euclidean Jordan algebras. The specificity of our method is to use a transformation similar to that introduced by Darvay and Takács for the centering equations of the central path of the linear optimization. The Nesterov and Todd symmetrization scheme is used to derive the search directions. The theoretical complexity bound of the algorithm coincides with the best-known iteration bound for small-update methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Kheirfam [18] extended the method to 𝑃 * (𝑘)-horizontal linear complementarity problems, while Guerra [16] applied it to the SDO case. For more related papers about Darvay and Takàcs' technique, we refer to (see e.g., [11,19,20]).…”
mentioning
confidence: 99%